Refinement of the Hounsfield look‐up table by retrospective application of patient‐specific direct proton stopping‐power prediction from dual‐energy CT. Issue 4 (29th February 2020) - Wohlfahrt, Patrick; Möhler, Christian; Enghardt, Wolfgang; Krause, Mechthild; Kunath, Daniela; Menkel, Stefan; Troost, Esther G. C.; Greilich, Steffen; Richter, Christian
Abstract : Background and Purpose: Proton treatment planning relies on an accurate determination of stopping‐power ratio (SPR) from x‐ray computed tomography (CT). A refinement of the heuristic CT‐based SPR prediction using a state‐of‐the‐art Hounsfield look‐up table (HLUT) is proposed, which incorporates patient SPR information obtained from dual‐energy CT (DECT) in a retrospective patient‐cohort analysis. Material and Methods: SPR datasets of 25 brain‐tumor patients, 25 prostate‐cancer patients, and three nonsmall cell lung‐cancer (NSCLC) patients were calculated from clinical DECT scans with the comprehensively validated DirectSPR approach. Based on the median frequency distribution of voxelwise correlations between CT number and SPR within the irradiated volume, a piecewise linear function was specified (DirectSPR‐based adapted HLUT). Differences in dose distribution and proton range were assessed for the nonadapted and adapted HLUT in comparison to the DirectSPR method, which has been shown to be an accurate and reliable SPR estimation method. Results: The application of the DirectSPR‐based adapted HLUT instead of the nonadapted HLUT reduced the systematic proton range differences from 1.2% (1.1 mm) to −0.1% (0.0 mm) for brain‐tumor patients, 1.7% (4.1 mm) to 0.2% (0.5 mm) for prostate‐cancer patients, and 2.0% (2.9 mm) to −0.1% (0.0 mm) for NSCLC patients. Due to the large intra‐ and inter‐patient tissue variability, range differences to DirectSPR larger than 1% remained for the adapted HLUT. Conclusions: The incorporation of patient‐specific correlations between CT number and SPR, derived from a retrospective application of DirectSPR to a broad patient cohort, improves the SPR accuracy of the current state‐of‐the‐art HLUT approach. The DirectSPR‐based adapted HLUT has been clinically implemented at the University Proton Therapy Dresden (Dresden, Germany) in 2017. This already facilitates the benefits of an improved DECT‐based tissue differentiation within clinical routine without changing the general approach for range prediction (HLUT), and represents a further step toward full integration of the DECT‐based DirectSPR method for treatment planning in proton therapy.